Determinan Penghambat Penyerapan Anggaran: Studi Empiris pada Provinsi Riau - Devina Rosa Sitepu; Tri Priyatmo; Rusdi Akbar (Direktorat Sistem Perbendaharaan, 2024)
The World Bank asserts that developing countries, such as Indonesia, encounter challenges in budget utilization, known as slow and back-loaded. This research aims to identify the factors that cause budget absorption to be not optimal in local governments in Riau Province. This research uses mixed methods with an explanatory sequential approach. Primary data was obtained from the results of questionnaire answers to 202 SKPD heads and FGDs by the BPKP Middle Auditor for Riau Province along with five representatives of the Head of BPKAD in Riau. Based on quantitative analysis, it was concluded that partially, external factors, namely concerns about being exposed to cases by APH, had the greatest influence on budget absorption, which was not yet optimal. The results of the qualitative analysis encourage benchmarking, professional relationship guidelines with APH, a two-year budget, as well as integration of procurement and risk management.